62058
|
1 |
(* Title: HOL/Library/Quadratic_Discriminant.thy
|
60162
|
2 |
Author: Tim Makarios <tjm1983 at gmail.com>, 2012
|
|
3 |
|
|
4 |
Originally from the AFP entry Tarskis_Geometry
|
|
5 |
*)
|
|
6 |
|
|
7 |
section "Roots of real quadratics"
|
|
8 |
|
|
9 |
theory Quadratic_Discriminant
|
|
10 |
imports Complex_Main
|
|
11 |
begin
|
|
12 |
|
63465
|
13 |
definition discrim :: "real \<Rightarrow> real \<Rightarrow> real \<Rightarrow> real"
|
|
14 |
where "discrim a b c \<equiv> b\<^sup>2 - 4 * a * c"
|
60162
|
15 |
|
|
16 |
lemma complete_square:
|
68553
|
17 |
"a \<noteq> 0 \<Longrightarrow> a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> (2 * a * x + b)\<^sup>2 = discrim a b c"
|
|
18 |
by (simp add: discrim_def) algebra
|
60162
|
19 |
|
|
20 |
lemma discriminant_negative:
|
|
21 |
fixes a b c x :: real
|
|
22 |
assumes "a \<noteq> 0"
|
63465
|
23 |
and "discrim a b c < 0"
|
60162
|
24 |
shows "a * x\<^sup>2 + b * x + c \<noteq> 0"
|
|
25 |
proof -
|
63465
|
26 |
have "(2 * a * x + b)\<^sup>2 \<ge> 0"
|
|
27 |
by simp
|
|
28 |
with \<open>discrim a b c < 0\<close> have "(2 * a * x + b)\<^sup>2 \<noteq> discrim a b c"
|
|
29 |
by arith
|
|
30 |
with complete_square and \<open>a \<noteq> 0\<close> show "a * x\<^sup>2 + b * x + c \<noteq> 0"
|
|
31 |
by simp
|
60162
|
32 |
qed
|
|
33 |
|
|
34 |
lemma plus_or_minus_sqrt:
|
|
35 |
fixes x y :: real
|
|
36 |
assumes "y \<ge> 0"
|
|
37 |
shows "x\<^sup>2 = y \<longleftrightarrow> x = sqrt y \<or> x = - sqrt y"
|
|
38 |
proof
|
|
39 |
assume "x\<^sup>2 = y"
|
63465
|
40 |
then have "sqrt (x\<^sup>2) = sqrt y"
|
|
41 |
by simp
|
|
42 |
then have "sqrt y = \<bar>x\<bar>"
|
|
43 |
by simp
|
|
44 |
then show "x = sqrt y \<or> x = - sqrt y"
|
|
45 |
by auto
|
60162
|
46 |
next
|
|
47 |
assume "x = sqrt y \<or> x = - sqrt y"
|
63465
|
48 |
then have "x\<^sup>2 = (sqrt y)\<^sup>2 \<or> x\<^sup>2 = (- sqrt y)\<^sup>2"
|
|
49 |
by auto
|
|
50 |
with \<open>y \<ge> 0\<close> show "x\<^sup>2 = y"
|
|
51 |
by simp
|
60162
|
52 |
qed
|
|
53 |
|
|
54 |
lemma divide_non_zero:
|
|
55 |
fixes x y z :: real
|
|
56 |
assumes "x \<noteq> 0"
|
|
57 |
shows "x * y = z \<longleftrightarrow> y = z / x"
|
|
58 |
proof
|
63465
|
59 |
show "y = z / x" if "x * y = z"
|
|
60 |
using \<open>x \<noteq> 0\<close> that by (simp add: field_simps)
|
|
61 |
show "x * y = z" if "y = z / x"
|
|
62 |
using \<open>x \<noteq> 0\<close> that by simp
|
60162
|
63 |
qed
|
|
64 |
|
|
65 |
lemma discriminant_nonneg:
|
|
66 |
fixes a b c x :: real
|
|
67 |
assumes "a \<noteq> 0"
|
63465
|
68 |
and "discrim a b c \<ge> 0"
|
60162
|
69 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
63465
|
70 |
x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
71 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
60162
|
72 |
proof -
|
|
73 |
from complete_square and plus_or_minus_sqrt and assms
|
|
74 |
have "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
75 |
(2 * a) * x + b = sqrt (discrim a b c) \<or>
|
|
76 |
(2 * a) * x + b = - sqrt (discrim a b c)"
|
|
77 |
by simp
|
|
78 |
also have "\<dots> \<longleftrightarrow> (2 * a) * x = (-b + sqrt (discrim a b c)) \<or>
|
|
79 |
(2 * a) * x = (-b - sqrt (discrim a b c))"
|
|
80 |
by auto
|
60500
|
81 |
also from \<open>a \<noteq> 0\<close> and divide_non_zero [of "2 * a" x]
|
60162
|
82 |
have "\<dots> \<longleftrightarrow> x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
83 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
|
84 |
by simp
|
|
85 |
finally show "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
|
86 |
x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
87 |
x = (-b - sqrt (discrim a b c)) / (2 * a)" .
|
|
88 |
qed
|
|
89 |
|
|
90 |
lemma discriminant_zero:
|
|
91 |
fixes a b c x :: real
|
|
92 |
assumes "a \<noteq> 0"
|
63465
|
93 |
and "discrim a b c = 0"
|
60162
|
94 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow> x = -b / (2 * a)"
|
63465
|
95 |
by (simp add: discriminant_nonneg assms)
|
60162
|
96 |
|
|
97 |
theorem discriminant_iff:
|
|
98 |
fixes a b c x :: real
|
|
99 |
assumes "a \<noteq> 0"
|
|
100 |
shows "a * x\<^sup>2 + b * x + c = 0 \<longleftrightarrow>
|
63465
|
101 |
discrim a b c \<ge> 0 \<and>
|
|
102 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
|
103 |
x = (-b - sqrt (discrim a b c)) / (2 * a))"
|
60162
|
104 |
proof
|
|
105 |
assume "a * x\<^sup>2 + b * x + c = 0"
|
63465
|
106 |
with discriminant_negative and \<open>a \<noteq> 0\<close> have "\<not>(discrim a b c < 0)"
|
|
107 |
by auto
|
|
108 |
then have "discrim a b c \<ge> 0"
|
|
109 |
by simp
|
60500
|
110 |
with discriminant_nonneg and \<open>a * x\<^sup>2 + b * x + c = 0\<close> and \<open>a \<noteq> 0\<close>
|
60162
|
111 |
have "x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
63465
|
112 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
60162
|
113 |
by simp
|
60500
|
114 |
with \<open>discrim a b c \<ge> 0\<close>
|
60162
|
115 |
show "discrim a b c \<ge> 0 \<and>
|
|
116 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
63465
|
117 |
x = (-b - sqrt (discrim a b c)) / (2 * a))" ..
|
60162
|
118 |
next
|
|
119 |
assume "discrim a b c \<ge> 0 \<and>
|
|
120 |
(x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
63465
|
121 |
x = (-b - sqrt (discrim a b c)) / (2 * a))"
|
|
122 |
then have "discrim a b c \<ge> 0" and
|
60162
|
123 |
"x = (-b + sqrt (discrim a b c)) / (2 * a) \<or>
|
63465
|
124 |
x = (-b - sqrt (discrim a b c)) / (2 * a)"
|
60162
|
125 |
by simp_all
|
63465
|
126 |
with discriminant_nonneg and \<open>a \<noteq> 0\<close> show "a * x\<^sup>2 + b * x + c = 0"
|
|
127 |
by simp
|
60162
|
128 |
qed
|
|
129 |
|
|
130 |
lemma discriminant_nonneg_ex:
|
|
131 |
fixes a b c :: real
|
|
132 |
assumes "a \<noteq> 0"
|
63465
|
133 |
and "discrim a b c \<ge> 0"
|
60162
|
134 |
shows "\<exists> x. a * x\<^sup>2 + b * x + c = 0"
|
63465
|
135 |
by (auto simp: discriminant_nonneg assms)
|
60162
|
136 |
|
|
137 |
lemma discriminant_pos_ex:
|
|
138 |
fixes a b c :: real
|
|
139 |
assumes "a \<noteq> 0"
|
63465
|
140 |
and "discrim a b c > 0"
|
|
141 |
shows "\<exists>x y. x \<noteq> y \<and> a * x\<^sup>2 + b * x + c = 0 \<and> a * y\<^sup>2 + b * y + c = 0"
|
60162
|
142 |
proof -
|
|
143 |
let ?x = "(-b + sqrt (discrim a b c)) / (2 * a)"
|
|
144 |
let ?y = "(-b - sqrt (discrim a b c)) / (2 * a)"
|
63465
|
145 |
from \<open>discrim a b c > 0\<close> have "sqrt (discrim a b c) \<noteq> 0"
|
|
146 |
by simp
|
|
147 |
then have "sqrt (discrim a b c) \<noteq> - sqrt (discrim a b c)"
|
|
148 |
by arith
|
|
149 |
with \<open>a \<noteq> 0\<close> have "?x \<noteq> ?y"
|
|
150 |
by simp
|
|
151 |
moreover from assms have "a * ?x\<^sup>2 + b * ?x + c = 0" and "a * ?y\<^sup>2 + b * ?y + c = 0"
|
|
152 |
using discriminant_nonneg [of a b c ?x]
|
|
153 |
and discriminant_nonneg [of a b c ?y]
|
|
154 |
by simp_all
|
|
155 |
ultimately show ?thesis
|
|
156 |
by blast
|
60162
|
157 |
qed
|
|
158 |
|
|
159 |
lemma discriminant_pos_distinct:
|
|
160 |
fixes a b c x :: real
|
63465
|
161 |
assumes "a \<noteq> 0"
|
|
162 |
and "discrim a b c > 0"
|
60162
|
163 |
shows "\<exists> y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0"
|
|
164 |
proof -
|
60500
|
165 |
from discriminant_pos_ex and \<open>a \<noteq> 0\<close> and \<open>discrim a b c > 0\<close>
|
60162
|
166 |
obtain w and z where "w \<noteq> z"
|
|
167 |
and "a * w\<^sup>2 + b * w + c = 0" and "a * z\<^sup>2 + b * z + c = 0"
|
|
168 |
by blast
|
63465
|
169 |
show "\<exists>y. x \<noteq> y \<and> a * y\<^sup>2 + b * y + c = 0"
|
|
170 |
proof (cases "x = w")
|
|
171 |
case True
|
|
172 |
with \<open>w \<noteq> z\<close> have "x \<noteq> z"
|
|
173 |
by simp
|
|
174 |
with \<open>a * z\<^sup>2 + b * z + c = 0\<close> show ?thesis
|
|
175 |
by auto
|
60162
|
176 |
next
|
63465
|
177 |
case False
|
|
178 |
with \<open>a * w\<^sup>2 + b * w + c = 0\<close> show ?thesis
|
|
179 |
by auto
|
60162
|
180 |
qed
|
|
181 |
qed
|
|
182 |
|
68553
|
183 |
lemma Rats_solution_QE:
|
|
184 |
assumes "a \<in> \<rat>" "b \<in> \<rat>" "a \<noteq> 0"
|
|
185 |
and "a*x^2 + b*x + c = 0"
|
|
186 |
and "sqrt (discrim a b c) \<in> \<rat>"
|
|
187 |
shows "x \<in> \<rat>"
|
|
188 |
using assms(1,2,5) discriminant_iff[THEN iffD1, OF assms(3,4)] by auto
|
|
189 |
|
|
190 |
lemma Rats_solution_QE_converse:
|
|
191 |
assumes "a \<in> \<rat>" "b \<in> \<rat>"
|
|
192 |
and "a*x^2 + b*x + c = 0"
|
|
193 |
and "x \<in> \<rat>"
|
|
194 |
shows "sqrt (discrim a b c) \<in> \<rat>"
|
|
195 |
proof -
|
|
196 |
from assms(3) have "discrim a b c = (2*a*x+b)^2" unfolding discrim_def by algebra
|
|
197 |
hence "sqrt (discrim a b c) = \<bar>2*a*x+b\<bar>" by (simp)
|
|
198 |
thus ?thesis using \<open>a \<in> \<rat>\<close> \<open>b \<in> \<rat>\<close> \<open>x \<in> \<rat>\<close> by (simp)
|
|
199 |
qed
|
|
200 |
|
60162
|
201 |
end
|